Bacillus velezensis GH1-13 enhances drought tolerance in rice by reducing the accumulation of reactive oxygen species - Park, Dongryeol; Jang, Jinwoo; Seo, Deok Hyun; Kim, Yangseon; Jang, Geupil (Frontiers in Plant Science, 2024)
Plant growth-promoting rhizobacteria colonize the rhizosphere through dynamic and intricate interactions with plants, thereby providing various benefits and contributing to plant growth. Moreover, increasing evidence suggests that plant growth-promoting rhizobacteria affect plant tolerance to abiotic stress, but the underlying molecular mechanisms remain largely unknown. In this study, we investigated the effect of Bacillus velezensis strain GH1-13 on drought stress tolerance in rice. Phenotypical analysis, including the measurement of chlorophyll content and survival rate, showed that Bacillus velezensis GH1-13 enhances rice tolerance to drought stress. Additionally, visualizing ROS levels and quantifying the expression of ROS-scavenging genes revealed that GH1-13 treatment reduces ROS accumulation under drought stress by activating the expression of antioxidant genes. Furthermore, the GH1-13 treatment stimulated the jasmonic acid response, which is a key phytohormone that mediates plant stress tolerance. Together with the result that jasmonic acid treatment promotes the expression of antioxidant genes, these findings indicate that Bacillus velezensis GH1-13 improves drought tolerance in rice by reducing ROS accumulation and suggest that activation of the jasmonic acid response is deeply involved in this process.